KEKUATAN SISTEM PAYROLL DALAM MENINGKATKAN POTENSI ZAKAT DI BAZNAS : (Evidence from BAZNAS Central Java Indonesia) - Yahya, Imam; Sahidin, Sahidin; Rohayana, Ade Dedi; Ananda, M Aflahmuna; Sopyan, Yayan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The research aims to analyze the digitalization of zakat, which is expected to be an excellent opportunity to realize the great potential of Muslim zakat in Indonesia. Various zakat platforms are distributed online, but not all platforms can be applied in real life in Muslim communities. This research also explains how civil servant salaries can be cut as a form of digital zakat platform implemented at Badan Amil Zakat Nasional (BAZNAS) Central Java. This research used qualitative methods and was conducted in-depth interview with several community leaders and Zakat and Muzakki activists. This research determine the strength of the payroll system in increasing zakat collection at BAZNAS Central Java. The results of the research showed the following: First, alary cuts for civil servants were carried out based on regional regulations, namely the Instructions of the Governor of Central Java from 2004-2019 regarding optimizing zakat management. Second, transparency and accountability in implementing zakat deductions and distribution at BAZNAS; third, the high level of trust of civil servant Muzakki to optimize zakat charity through BAZNAS. From this research, an implication can be formulated that using online platforms can increase awareness of paying zakat for government civil servants at BAZNAS Central Java.